Design and synthesis of an activity-based protein profiling probe derived from cinnamic hydroxamic acid. Issue 4 (15th February 2016) - Ai, Teng; Qiu, Li; Xie, Jiashu; Geraghty, Robert J.; Chen, Liqiang
Graphical abstract: Abstract: In our continued effort to discover new anti-hepatitis C virus (HCV) agents, we validated the anti-replicon activity of compound1, a potent and selective anti-HCV hydroxamic acid recently reported by us. Generally favorable physicochemical and in vitro absorption, distribution, metabolism, and excretion (ADME) properties exhibited by1 made it an ideal parent compound from which activity-based protein profiling (ABPP) probe3 was designed and synthesized. Evaluation of probe3 revealed that it possessed necessary anti-HCV activity and selectivity. Therefore, we have successfully obtained compound3 as a suitable ABPP probe to identify potential molecular targets of compound1 . Probe3 and its improved analogs are expected to join a growing list of ABPP probes that have made important contributions to not only the studies of biochemical and cellular functions but also discovery of selective inhibitors of protein targets.